Efforts to Improve Social Studies Instruction to Address Low Student Motivation - Nuning Christiana; Rifa'i Rifa'i (Jurnal Pendidikan Rafflesia, 2026)
This study aims to describe the efforts to develop social studies (IPS) learning to overcome the low learning motivation of students. Low student motivation in social studies subjects is a problem commonly found at various educational levels. This is caused by various factors, including monotonous teaching methods, lack of relevance of the material to daily life, and minimal use of innovative learning media. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, in-depth interviews, and documentation. The research subjects were social studies teachers and eighth-grade students at SMP Negeri 5 Bandung City. The results show that the development of social studies learning through the application of contextual learning models, technology-based media usage, and project-based approaches can significantly increase student learning motivation. The implications of this research can serve as a reference for teachers in designing and developing more effective and enjoyable social studies learning strategies.